2009
DOI: 10.1080/03014460802660526
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of overweight associated with stunting in preschool children of Yaoundé, Cameroon

Abstract: Poor preschool children of Yaounde are facing concomitant stunting and overweight. More studies are needed to better assess the impact of maternal factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 39 publications
3
61
0
Order By: Relevance
“…An ecological study conducted in Mexico found that maternal factors (short maternal stature, lower maternal age, level of education and perceived social status) and household properties (living in large household, a low socio-economic status) are independent factors associated with the coexistence of overweight and stunting in preschool children [10]. In Yaoundé, the capital city of Cameroon, we previously found that a low socio-economic status, a low level of maternal education and maternal under-evaluation of children’s weight are independent risk factors for these children to be simultaneaously stunted and overweight [11].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…An ecological study conducted in Mexico found that maternal factors (short maternal stature, lower maternal age, level of education and perceived social status) and household properties (living in large household, a low socio-economic status) are independent factors associated with the coexistence of overweight and stunting in preschool children [10]. In Yaoundé, the capital city of Cameroon, we previously found that a low socio-economic status, a low level of maternal education and maternal under-evaluation of children’s weight are independent risk factors for these children to be simultaneaously stunted and overweight [11].…”
Section: Introductionmentioning
confidence: 93%
“…In fact, during the last two decades, epidemiological studies have revealed that children and adolescents living in countries undergoing nutrition transition can be simultaneously growth retarded and overweight [5][11]. An ecological study conducted in Mexico found that maternal factors (short maternal stature, lower maternal age, level of education and perceived social status) and household properties (living in large household, a low socio-economic status) are independent factors associated with the coexistence of overweight and stunting in preschool children [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, a great percentage of individuals who experienced chronically poor nutrition in their early lives, and are thus stunted, seem to be more predisposed to obesity later in life (Florencio et al, 2003(Florencio et al, , 2007Martins et al, 2004;Grillo et al, 2005;Romaguera et al, 2008;Said-Mohamed et al, 2009;Ferreira et al, 2009;Sichieri et al, 2010;Alves et al, 2011). Individuals with chronic under-nutrition (stunting) in early life seem to have reduced energetic demands through metabolic (Soares-Wynter and Walker, 1996;Frisancho, 2003;Grillo et al, 2005;Said-Mohamed et al, 2009 and behavioral shifts (Spurr and Reina, 1988;Hoffman et al, 2000;Wilson et al, 2012).…”
mentioning
confidence: 93%
“…Individuals with chronic under-nutrition (stunting) in early life seem to have reduced energetic demands through metabolic (Soares-Wynter and Walker, 1996;Frisancho, 2003;Grillo et al, 2005;Said-Mohamed et al, 2009 and behavioral shifts (Spurr and Reina, 1988;Hoffman et al, 2000;Wilson et al, 2012). Such reduced energetic demands may increase an individual's odds of immediate survival under conditions of energetic stress yet have negative longer-term consequences in health and survival.…”
mentioning
confidence: 96%